Dinamika Motivasi Belajar Siswa dalam Pembelajaran Bahasa Arab dan Strategi Penguatannya - Widayanti, Linda; Hajam, Hajam; Taqiyuddin, Taqiyuddin (Study Program of Arabic Language Teaching, 2026)
This study aims to examine the dynamics of student motivation for Arabic language learning and strategies to strengthen it at Madrasah Aliyah Hasbullah Karanganyar Pekalongan. Learning motivation is a fundamental component that determines the success of the learning process, especially in Arabic language learning, which has its own linguistic characteristics such as the right-to-left writing system, naḥwu and ṣarf rules, and complex vocabulary (mufradāt). This study uses a qualitative case study design. Primary data were obtained through in-depth interviews with two Arabic language teachers, one madrasah principal, and 12 students selected purposively from grades X, XI, and XII, as well as through participatory observation during the learning process. Secondary data were obtained from documentation, including curriculum documents, grade recaps, and madrasah profile data, for the 2023/2024 Academic Year, covering 202 students and 14 honorary educators. Data analysis used the interactive model of Miles, Huberman, and Saldaña. The results of this study indicate that student learning motivation is dynamic and influenced by internal factors including interest, self-efficacy, and clarity of learning goals, as well as external factors including teacher teaching quality, classroom climate, and family support. Effective motivation-boosting strategies include innovative learning media, a communicative approach, and appreciation-based reinforcement. This research is expected to contribute to the development of Arabic language learning at the Islamic high school level.